Mechanical effect and load transfer mechanism of soft rock tunnel composite lining considering creep effect - Xu, Jianbo; Fang, Juntao; Jiang, Ping; Han, Aiguo; Jiang, Cheng; Sun, Qinghui; Song, Jianjun; Lin, Hang; Ren, Ruowei; Zuo, Changqun (Frontiers in Earth Science, 2025)
Taking the Xianfeng Tunnel in Luzhai county, Guangxi province as the engineering background, this study aims to investigate the influence of different construction parameters on the stress and deformation of lining structures under creep effects, and also reveal the load-sharing ratios of composite lining structures under varying initial support stiffness conditions and the temporal evolution patterns and transfer mechanisms of surrounding rock pressure by using field monitoring and numerical simulation methods. The findings of this research are as follows: (1) Both monitoring data and simulation analyses demonstrate that the Cvisc constitutive model effectively describes the creep behavior of the surrounding rock in the engineering area; (2) Construction parameters have a significant impact on the stress of the primary lining, the earlier application of the secondary lining leading to greater structural stress; (3) With the increase of the elastic modulus of the primary lining, the load-sharing ratio of the secondary lining decreases, while the ultimate pressure borne by the secondary lining remains relatively stable; (4) Considering the time-dependent effects of creep behavior, when the secondary support is installed before the yield phase of initial structure, the pressure on each part of the lining structure is distributed according to the stiffness of each structure; subsequently, as the initial support enters the yield phase, the load it bears transferred to the secondary lining structure. These research findings can provide theoretical guidance for the design of support structures and construction parameters in soft rock tunnels.